Prevalence of Helicobacter pylori among residents and their environments in the Nara prefecture, Japan - Saori Horiuchi; Ryuichi Nakano; Akiyo Nakano; Naokuni Hishiya; Kenji Uno; Yuki Suzuki; Naoki Kakuta; Risako Kakuta; Kohsuke Tsubaki; Noriko Jojima; Hisakazu Yano (Elsevier, 2021)
Background: Chronic infection with Helicobacter pylori, specifically cagA-positive strains, is associated with gastric cancer. Thus, measures to prevent H. pylori infection are required. This study was conducted to clarify the prevalence of H. pylori in the community to identify the infection source and comprehensively assess the risk of H. pylori infection. Methods: We collected 90 human faecal samples and 73 environmental samples (water, vegetable, and animal faecal samples) from the residents in an area with a high incidence of gastric cancer in Japan. Polymerase chain reaction assay was performed to detect the glmM housekeeping gene and the cagA virulence gene of H. pylori. A questionnaire survey was conducted, and the responses were analyzed statistically. Results: The glmM gene was detected in 18 of 90 (20%) faecal samples obtained from residents; among them, the cagA gene was detected in 33.3% (6/18), and in all who had undergone eradication therapy. H. pylori was not detected in environmental samples. However, contact with dogs (OR 3.89, 95% CI 1.15-13.15, P < 0.05) was associated with higher odds for glmM gene positivity in the questionnaire survey. Conclusions: The prevalence of H. pylori and cagA-positive strains among the residents was low. However, the study results suggest a correlation between recurrent infection and cagA-positive H. pylori strains. Although H. pylori genes were not detected in living environments, an association between contact with dogs and a glmM positive status was revealed. Further investigations targeting community-dwelling healthy people and their living environments would be required for H. pylori infection control.